The No Child Left Behind legislation : educational research and federal funding - Carlson, Jerry S.; Levin, Joel R. (Psychological perspectives on contemporary educational issues., 2005)
With the publication of this book, the scholarly journal Issues in Education: Contributions from Educational Psychology is moving to a book series publication format. Carlson (University of California-Riverside) and Levin (University of Arizona) present material on aspects of the No Child Left Behind legislation.